THE EFFECT OF NATURAL FIBER (BANANA FIBER) ON THE MECHANICAL PROPERTIES OF SELF-COMPACTING CONCRETE - Chairunnisa, Nursiah; Nurwidayati, Ratni; Muhammad Madani S, Gusti (Journal of Applied Engineering Science, 2022)
Self-compacting concrete is an innovative concrete technology with higher flowability properties by adding the mineral admixtures such as superplasticizers and not necessary to vibrate concrete. The banana fibers were used in this investigation because banana fiber is an environmentally friendly material with good properties compared to synthetic fiber. The experimental test consisted of two phases of research, i.e., preliminary research, which had the aim to investigate the appropriate percentage of superplasticizer in the mixed composition of self-compacting concrete. The percentages of superplasticizers were 0.7%, 1%, and 1.4%. The second phase of research on the effect of additional banana fiber on self-compacting concrete was carried out, examining workability, compressive strength, and the splitting tensile strength of concrete. In this research, the percentages of fiber were 0.12%, 0.3%, and 0.5% of the cement weight, and evaluated the effect of fiber treatment. The treated fibers mean that the fiber is immersed in NaOH solution or named as a delignification process. The hardened concrete specimen was used for determining the mechanical strengths, such as the compressive strength and split tensile strength tests. The test results found that the optimum value for superplasticizer dosage was 0.7% of cement weight, which can fulfill the whole criteria of fresh concrete and hardened SCC concrete. Furthermore, the specimen with the adding banana fiber of 0.12% by cement weight and treated fiber indicated a decrease in workability. Compared to the control concrete, it inversely increased compressive strength up to 44.36% and tensile strength up to 17.78%.